GMNN and DLL1 mutation-related spondylocarpotarsal synostosis: a case report - Joonhwan Lee; Byungju Ryu; Yunhee Kim; Eunyoung Lee (Journal of Yeungnam Medical Science)
Spondylocarpotarsal synostosis syndrome (SCTS) is a rare genetic disorder characterized by vertebral fusion, short stature, and skeletal anomalies. SCTS is primarily associated with mutations in filamin B. However, in this report, we present a unique case of SCTS in a 28-year-old male who complained of neck and shoulder pain persisting for 1 year. His clinical presentation included radioulnar synostosis, cervical spine anomalies (scoliosis and agenesis of the posterior arch of C1), and a history of polydactyly. Genetic analysis revealed mutations in GMNN and DLL1. To the best of our knowledge, this is the first report on the association of SCTS with these genes.